Political refugees in ancient Rome - (O.): Bräckel - Flucht auswärtiger Eliten ins Römische Reich. Asyl und Exil - Havener, Wolfgang (The classical review, 2022)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0009840X22000622/resource/name/firstPage-S0009840X22000622a.jpg
Gesehen am 06.09.2023
Keywords: Rezension